Pelatihan Pembukuan Akuntansi Sederhana untuk Meningkatkan Keunggulan Kinerja - Septiani, Dwi; Ferdiansyah, Ferdiansyah; Sunarto, Sunarto; Sagantha, Fitri (Journal Pemberdayaan Masyarakat Indonesia, 2022)
The very fast and dynamic business development as well as the increasing level of business competition between competitors requires Micro, Small and Medium Enterprises (MSMEs) to move quickly to keep up with the times. In addition to marketing, MSME actors also need to prepare as well as possible the management of the 'home industry' for the survival of a business, such as readiness for business management, business financial management, stock management and customer service management. Of course, this preparation cannot be done alone, moreover not all MSMEs understand the whole problem, so MSME actors need to be assisted and assisted. The community service program held at MSME Karani Craft aims to train MSMEs in simple accounting books so that in the future MSMEs can create superior accounting performance through simple accounting bookkeeping. The implementation method in this service activity is training. MSME actors are trained and guided to do simple accounting records in the form of income and expenses. These activities are carried out in a sustainable, measurable manner and the process of monitoring and evaluation is to measure the achievement of targets and expected results, namely making MSME actors able to carry out simple bookkeeping to create accounting performance excellence for MSMEs.